Tucker & Dale vs. evil [videorecording (Blu-Ray)] - Craig, Eli, 1972-; Jurgenson, Morgan; Labine, Tyler, 1978-; Tudyk, Alan; Bowden, Katrina, 1988-; Moss, Jesse, 1983- (Magnet Home Entertainment : Magnolia Home Entertainmet, 2011)
Two friends on vacation at their dilapidated mountain house are mistaken for murderous backwoods hillbillies by a group of obnoxious, preppy college kids. When one of the students is separated from the group, the boys try to lend a hand, but as the misunderstanding grows, so do the body count and the laughs.